WORKSHOP ON PROCESSING MUSTARD GREENS INTO SNACK PRODUCTS TO INCREASE MARKETING OF AGRICULTURAL PRODUCTS IN RIANGGEDE VILLAGE, TABANAN, BALI - Pratiwi, Nuning Indah; Yuda Pratama, I Putu; Indra Satria, Wahyu (LPPM Univ. Ibn Khaldun Bogor, 2023)
Community service activities in the form of workshops on processing mustard hujai into snack products to improve the marketing of agricultural products aim to, improve the skills of PKK mothers starting from the selection of raw materials, processing, and packaging to the market level of PKK mothers in the use of agricultural products in Rianggede village, improving their welfare. This workshop aims to make every PKK mother additional income that can prosper her family. Training objectives are achieved through presentations, demonstrations, tutorials, and question-and-answer procedures. After the training, there is a follow-up or evaluation and the support of the committee (students) to see PKK mothers and help them prepare snacks (mustard sticks) and prepare products for sale. The results showed that the community service program training went well and successfully. This training program can equip mothers with plant-based snack production skills (mustard sticks) and improve their welfare through income from the sale of these processed products. Problems or obstacles that arise during the training phase can be overcome with mentoring methods. Regarding criticism and suggestions about the results of the work program, farmer group mothers are expected to be enthusiastic and motivated to further develop this business. It is hoped that education experts can always help women in Rianggede Village and Rianggede Village benefit from theoretical and practical contributions.